The General Motor Ability Hypothesis: An Old Idea Revisited. Issue 2 (April 2018) - Hands, Beth; McIntyre, Fleur; Parker, Helen
While specific motor abilities have become a popular explanation for motor performance, the older, alternate notion of a general motor ability should be revisited. Current theories lack consensus, and most motor assessment tools continue to derive a single composite score to represent motor capacity. In addition, results from elegant statistical procedures such as higher order factor analyses, cluster analyses, and Item Response Theory support a more global motor ability. We propose a contemporary model of general motor ability as a unidimensional construct that is emergent and fluid over an individual's lifespan, influenced by both biological and environmental factors. In this article, we address the implications of this model for theory, practice, assessment, and research. Based on our hypothesis and Item Response Theory, our Lifespan Motor Ability Scale can identify motor assessment tasks that are relevant and important across varied phases of lifespan development.